Changes in the rate of nicotine metabolism across pregnancy: a longitudinal study - Bowker, Katharine; Lewis, Sarah; Coleman, Tim; Cooper, Sue (Wiley, 2015)
Aims: Increased nicotine metabolism during pregnancy could explain why nicotine replacement therapy (NRT) appears to be less effective on smoking cessation in pregnancy than in non-pregnant smokers, but little is known about nicotine metabolism across pregnancy. This study was conducted to determine when changes in nicotine metabolism occur during pregnancy and to describe the magnitude of these changes.